Exploring the Prerequisites for Transforming School as a Learning Organization - Khay, Sambonin (Central European Journal of Educational Research, 2024)
The organization model has shifted from treating the workforce as machines to improving human centricworking environments. The Learning Organization is conceptualized as an organism that evolves through continuous learning to adapt with a constantly changing environment. School is a typical organization and many scholars argued to reconceptualize school as a learning organization. The Integrated Model of School as a Learning Organization (Kools & Stoll, 2016)) has been widely studied and tested in European schools, particularly in Wales. However, there is a gap in the research needed to understand the prerequisites of SLO transformation and thus to better prepare for reform. To explore the prerequisites of SLO, a researcher applies a qualitative approach to purposely collect secondary data from the eight empirical studies in Wales, Greece, Latvia, Spain, Bulgaria, Türkiye, and Italy. To conduct data analysis, a data coding strategy is employed to create the prerequisites and assign them to the main themes- System Level and School Level. To achieve the SLO transformation, the researcher then recommends a systematic reform that involves the education stakeholders, both at system level and at school level - to put forward the practice of the SLO seven actionoriented dimensions. Further meta-analysis research is recommended to widen the scope of conceptualizing antecedents of SLO transformation.